2007
DOI: 10.4161/cbt.6.2.3577
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces G2/M arrest and apoptosis in cisplatin-resistant human ovarian cancer cells by modulating akt and p38 mAPK

Abstract: AcKNoWLedgeMeNTSWe acknowledge the financial support from the NIH grant CA 102264. AbSTRAcTCurcumin, a major active component of turmeric, is known to induce apoptosis in several types of cancer cells, but little is known about its activity in chemoresistant cells. Hence, the aim of the present study was to investigate the anticancer properties of curcumin in cisplatin-resistant human ovarian cancer cells in vitro. The results indicated that curcumin inhibited the proliferation of both cisplatin-resistant (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
171
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(193 citation statements)
references
References 48 publications
18
171
1
3
Order By: Relevance
“…Activation of caspase-3 followed by PARP cleavage is critical for triggering apoptosis in many cells (Elmore, 2007). It has been reported that curcumin induces apoptosis in cisplatin-resistant human ovarian cancer cells via activation of caspase-3 and degradation of PARP (Weir et al, 2007). Similarly, our present data revealed that miR-9 overexpression resulted in activation of caspase-3 and cleavage of PARP in SKOV3 cells, which confirmed the pro-apoptotic activity of miR-9 at the molecular level.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Activation of caspase-3 followed by PARP cleavage is critical for triggering apoptosis in many cells (Elmore, 2007). It has been reported that curcumin induces apoptosis in cisplatin-resistant human ovarian cancer cells via activation of caspase-3 and degradation of PARP (Weir et al, 2007). Similarly, our present data revealed that miR-9 overexpression resulted in activation of caspase-3 and cleavage of PARP in SKOV3 cells, which confirmed the pro-apoptotic activity of miR-9 at the molecular level.…”
Section: Discussionsupporting
confidence: 87%
“…Phenethyl isothiocyanate, acting as an inhibitor of EGFR-Akt axis, has been shown to suppress ovarian tumor growth in a preclinical mouse model (Loganathan et al, 2012). Curcumin has been shown to inhibit Akt phosphorylation in ovarian cancer cells (Weir et al, 2007). Consistently, we also observed the inhibitory effects of curcumin on Akt activation in SKOV3 cells.…”
Section: Discussionsupporting
confidence: 85%
“…Inhibition of cell growth and induction of apoptosis is the common mechanism by which curcumin shows its anticancer effects. Accumulating evidence suggests the involvement of multiple-signaling pathways by which curcumin causes growth suppression of human cancer cells (Cheng et al, 2001;Hidaka et al, 2002;Bharti et al, 2003;Kim et al, 2003;Shishodia et al, 2003;Blasius et al, 2006;Lev-Ari et al, 2006;Mitra et al, 2006;Park et al, 2006;Tan et al, 2006;Aggarwal et al, 2007;Aoki et al, 2007;Deeb et al, 2007;Fahey et al, 2007;Lin et al, 2007Lin et al, , 2008Marín et al, 2007;Shankar and Srivastava, 2007;Srivastava et al, 2007;Weir et al, 2007;Binion et al, 2008;Freudlsperger et al, 2008;Ji et al, 2008;Kasinski et al, 2008;Mackenzie et al, 2008;Shankar et al, 2008;Sun et al, 2008). Phase I clinical trials of curcumin demonstrated encouraging chemopreventive effects in patients with high-risk or pre-malignant lesions.…”
mentioning
confidence: 99%
“…This was shown for multidrug resistant myeloid leukemia cells (Lu et al, 2012), cisplatin resistant ovarian cancer cells (Weir et al, 2007), multiple myeloma cells resistant to 4 4 dexamethasone, doxorubicin and melphalan (Sung et al, 2009), as well as hormone independent, multidrug resistant breast cancer cells (Labbozzetta et al, 2009). …”
Section: Introductionmentioning
confidence: 80%
“…The drugs that could be efficient against chemoresistant cells could be of great importance in enhancing effectiveness of cancer treatment. There are some data in the literature that verified anticancer properties of curcumin in drug resistant cells (Labbozzetta et al, 2009;Lu et al, 2012;Sung et al, 2009;Weir et al, 2007). However, these data should be more abundant in order to make more general conclusions about curcumin's activity against drug resistant cells.…”
Section: Discussionmentioning
confidence: 99%